Características de productos farmacéuticos pesquisados por la Ufremid en la región La Libertad – 2014 - Villalobos Bernabé, Milagros Marissé (2015)
The present study aims to determine the characteristics of the pharmaceutical products investigated by the UFREMID during the year 2014, taking into account type of pharmaceutical establishment; pharmaceutical form, pharmacological group, origin of manufacture, compliance with the technical specifications authorized on your registration according to laboratory of origin. It is processed and analyzed the database, registered from the proceedings of the UFREMID research. The results allowed to determine that the type of pharmaceutical establishment with highest percentage of researched drugs were drugstores with a 63%, the pharmaceutical form pesquisada most frequently were the tablets with a 48%, the most frequent pharmacological group to which belong the researched medicines was antibiotics with 37%, researched products were mostly of national origin with a 65% for compliance with technical specifications authorized on his registration as laboratory of origin comply with 17% of laboratories Medrock products and violated by 52% products from laboratories Dany. It is concluded that the investigations carried out by the UFREMID determined that pharmaceuticals are safe, effective and quality, in order to protect the health of the population.